The History of Mr. Polly Based on a Novel by H.G. Wells - Pelissier, Anthony; Dickinson, Desmond; Mills, John; Davies, Betty Ann; Jenkins, Megs (John Mills Centenary Collection I)
Mr Alfred Polly (John Mills) is a sensitive soul. His job as a draper’s assistant does not suit him at all and when, one day he is sacked for daydreaming, he despairs of ever finding another job. His father’s death suddenly brings him a large inheritance, and with it he purchases a bike and sets off to find adventure. He meets and falls desperately in love with a young schoolgirl (Sally Ann Howes), but the relationship turns sour when her friends hear of it. Spurned, he hastily marries his cousin, Miriam (Betty Ann Davies), and settles in a sleepy town where he opens a draper’s shop. Fifteen years later, his life unfulfilled, unhappily married to a domineering spouse, and almost bankrupt, it’s time for him to make decisions ... Sparkling Victorian comedy drama based on H.G. Wells classic novel. Writer/director Anthony Pelissier’s screenplay is pleasantly faithful to its source material and the exceptionally engrossing John Mills gives one of the finest performances of his career. [www.britmovie.co.uk]